Assessment of Roundup Ready 2 (RR2) corn subjected to application of isolated and associated herbicides - Albrecht, Alfredo Junior Paiola; Albrecht, Leandro Paiola; Krenchinski, Fábio Henrique; Wobeto, Katle Samaya; Mattiuzzi, Mateus Dalpubel; Eckert, Caroline Thaís; Carbonari, Caio Antonio [UNESP]; Filho, Ricardo Victoria (Southern Cross Publishing, 2017)
One of the first transgenic traits that has been inserted into commercial crops and being widely used is tolerance to glyphosate herbicide. This technology has provided significant benefits and conveniences to farmers due to the efficacy of glyphosate. However, for a better weed control and prevention of weed resistant biotypes the use of two or more mechanisms is recommended practice. The combination of herbicides is the subject of several studies especially evaluating weed control, aside which the selectivity of the culture is equally important. In this context, this study aimed to evaluate the responses of transgenic corn (RR2) subjected to the application of different herbicides. For this purpose, an experiment was conducted with eight treatments using glyphosate, atrazine and nicosulfuron, sole or in combination along with a control treatment (without herbicide). The experiment was performed twice (first in Piracicaba - SP then Palotina - PR) in greenhouse with different corn hybrids. Several variables related to the performance were analysed such as height measurements, stem diameter, chlorophyll index, fresh and dry shoot, root dry mass. The results showed that nicosulfuron should be positioned cautiously in new RR2 corn hybrids, as it may damage the development of the plant.
Keywords: Roundup Ready 2 Technology; Selectivity; Transgenic Crops; Zea mays